Primary Psychosis: Risk and Protective Factors and Early Detection of the Onset - Claudio Brasso; Benedetta Giordano; Cristina Badino; Silvio Bellino; Paola Bozzatello; Cristiana Montemagni; Paola Rocca (Diagnostics, 2021)
Primary psychosis, which includes schizophrenia and other psychoses not caused by other psychic or physical conditions, has a strong impact worldwide in terms of disability, suffering and costs. Consequently, improvement of strategies to reduce the incidence and to improve the prognosis of this disorder is a current need. The purpose of this work is to review the current scientific literature on the main risk and protective factors of primary psychosis and to examine the main models of prevention, especially those related to the early detection of the onset. The conditions more strongly associated with primary psychosis are socio-demographic and economic factors such as male gender, birth in winter, ethnic minority, immigrant status, and difficult socio-economic conditions while the best-established preventive factors are elevated socio-economic status and an economic well-being. Risk and protective factors may be the targets for primordial, primary, and secondary preventive strategies. Acting on modifiable factors may reduce the incidence of the disorder or postpone its onset, while an early detection of the new cases enables a prompt treatment and a consequential better prognosis. According to this evidence, the study of the determinants of primary psychosis has a pivotal role in designing and promoting preventive policies aimed at reducing the burden of disability and suffering of the disorder.